Answer:
x = -3
Explanation:
Solve for x:
-2 (x - 4) = 14
Hint: | Divide both sides by a constant to simplify the equation.
Divide both sides of -2 (x - 4) = 14 by -2:
(-2 (x - 4))/(-2) = 14/(-2)
Hint: | Any nonzero number divided by itself is one.
(-2)/(-2) = 1:
x - 4 = 14/(-2)
Hint: | Reduce 14/(-2) to lowest terms. Start by finding the GCD of 14 and -2.
The gcd of 14 and -2 is 2, so 14/(-2) = (2×7)/(2 (-1)) = 2/2×7/(-1) = 7/(-1):
x - 4 = 7/(-1)
Hint: | Simplify the sign of 7/(-1).
Multiply numerator and denominator of 7/(-1) by -1:
x - 4 = -7
Hint: | Isolate terms with x to the left hand side.
Add 4 to both sides:
x + (4 - 4) = 4 - 7
Hint: | Look for the difference of two identical terms.
4 - 4 = 0:
x = 4 - 7
Hint: | Evaluate 4 - 7.
4 - 7 = -3:
Answer: x = -3